1990
DOI: 10.1002/hep.1840110316
|View full text |Cite
|
Sign up to set email alerts
|

Early Involvement of Hepatic Parenchymal Cells in Erythrohepatic Protoporphyria? An Ultrastructural Study of Patients With and Without Overt Liver Disease and the Effect of Chenodeoxycholic Acid Treatement

Abstract: Liver biopsy specimens obtained from two groups of erythrohepatic protoporphyria patients were studied histopathologically and ultrastructurally. Group 1 comprised seven erythrohepatic protoporphyria patients with a normal liver histology; from two patients liver biopsy specimens were available before and after 1 yr of chenodeoxycholic acid treatment. Group 2 consisted of four patients with a history of liver disease and liver histopathology; three patients were observed before and after 1 yr of chenodeoxychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Accumulation ofprotoporphyrin has been detected as brown pigments in hepatocytes, Kupffer cells and biliary canaliculae. A recent study (29) concluded that ultrastructural changes in the hepatic parenchymal cells are present in early stages ofthe disease. Moreover, biliary canalicular abnormalities responsible for cholestasis were observed, similar to that described in rat livers perfused with protoporphyrin (30).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation ofprotoporphyrin has been detected as brown pigments in hepatocytes, Kupffer cells and biliary canaliculae. A recent study (29) concluded that ultrastructural changes in the hepatic parenchymal cells are present in early stages ofthe disease. Moreover, biliary canalicular abnormalities responsible for cholestasis were observed, similar to that described in rat livers perfused with protoporphyrin (30).…”
Section: Discussionmentioning
confidence: 99%
“…Protoporphyria is an autosomal dominant disease that is characterized biochemically by elevated protoporphyrin levels and clinically by photosensitivity and hepatobiliary disease (18). A rare but severe clinical sequela of protoporphyria is liver failure, leading to orthotopic liver transplantation or death (19)(20)(21).…”
mentioning
confidence: 99%
“…The first was choledocholithiasis, which is a well-known complication of EPP [7,25,31,32]. However, in our patient, the gallbladder had been previously removed.…”
Section: Discussionmentioning
confidence: 62%